Marx's law of value: a critique of David Harvey. Issue 1 (March 2020) - Roberts, Michael
In 2018, Professor David Harvey, the human geographer and the eminent scholar of Marx's works and their modern relevance, wrote a short paper entitled 'Marx's refusal of the labour theory of value'. In this paper, Harvey presents a series of theoretical confusions. The dual nature of value in a commodity is ignored by him. So Marx's theory of crisis (based on insufficient surplus value) is replaced with insufficient use values for workers as consumers. The class struggle becomes not workers versus capitalists, but consumers versus capitalists or taxpayers versus governments. This is confusing to a class analysis and strategy for the working-class struggle.